(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2017)
In hydrological modeling the roughness coefficient is a parameter of great importance as it determines the degree of resistance offered by the bottom and walls of a channel or a basin to the flow of water, however, taking into account that the values of reference for this parameter has a hydraulic approach and in order to obtain more precise and accurate results with reality, this work seeks to determine a roughness coefficient of hydrological character for basins with a forest cover vegetation from the calibration of the same with a distributed hydrological model as is the Iber.